The application of objective structured clinical examinations for evaluating clinical internship in long-term clinical medical students in China - Yang, Miao; Liu, Yao; Dong, Yuhan; Ding, Yang; Lu, Zhibing; Yu, Mingxia; He, Xingxing (Frontiers in Education, 2025)
BackgroundClinical internship plays a vital role in enhancing medical students’ theoretical knowledge, clinical operational abilities, and clinical thinking development. This study aims to establish an efficient evaluation system to assess interns’ proficiency in clinical skills, and analyze the teaching effectiveness of clinical internships.MethodsThis is a retrospective descriptive study. A total of 75 long-term clinical medical students, including 26 eight-year students and 49 “5 + 3” students, who had already completed a 3-month clinical internship in internal medicine, participated in an Objective Structured Clinical Examination (OSCE). Four stations during the OSCE included history taking, abdominal physical examination, thoracentesis, and interpretation of auxiliary examination results. Both candidates and examiners voluntarily completed anonymous Likert scale questionnaire immediately after the OSCE. Results were analyzed using the Chi-square test and the t-test as appropriate.ResultsIn history taking station, new examiners awarded significantly higher scores compared to examiners with experience in conducting examinations (t = 6.21, p < 0.0001). “5 + 3” candidates scored significantly higher than 8-year clinical medicine doctoral program candidates in physical examination and thoracentesis station (t = 5.316, p < 0.0001; and t = 2.145, p = 0.0353, respectively). According to the questionnaire survey, the majority of candidates and all examiners were quite satisfied with its design, organization, quality and effectiveness. More than half of the candidates and examiners believed that insufficient practice and inadequate preparation for revision were the factors most likely to affect performance. 75% of the examiners felt that candidates needed the most training in operative steps and content, but only 56 and 40% of the candidates agreed with this view. Furthermore, 56% of candidates and half of the examiners identified operational methods and humanistic care as areas that still required intensive improvement.ConclusionThis study is an effective attempt to construct an OSCE evaluation system for the skills of long-term clinical medical students in the internship stage. This system can objectively and comprehensively reflect the students’ clinical skills, promote the realization of evaluation feedback and quality management of clinical internship teaching, which can be promoted in the evaluation of clinical internship.